Entrevior au travers agen manajemen psychological reactance penanganan dampak Covid-19 dalam Perspektif Ekonomi Syariah - Hifi Rini Puspita (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2022)
This research was conducted with the aim of briefly answering the “entrevior au travers” concrete steps of management agents shown by Islamic sharia on psychological reactance to handling the impact of Covid-19 from a sharia economic perspective. This study uses a qualitative descriptive analytical approach. The data were collected using literature study techniques and documentation studies. Its features include a glossary, references, website, source notes, and indexes. The data were analyzed using qualitative analysis approaches and techniques. The results of this study conclude: 1) The study of dialogue between religion and psychology, although it is difficult because psychologists often do not have a strong understanding of religious traditions, this pandime becomes a moment to understand the basic problems and materials to link religion with psychology. 2) Longitudinal and cross-sectional studies should seek common ground that supports the theory of a better spirituality - physical health - mental correlation through religious implementation. 3) Religion teaches a positive impact on mental health through religious activities on health measures, social support, and increases self-efficacy and cohesion.